Student Development in College : Theory, Research, and Practice - Evans, Nancy J. et.al (San Francisco Jossey-Bass, 2010)
Offers higher education professionals an understanding of the developmental challenges facing by college students. This title includes integrative theories of student development, coverage of social identity theories, a targeted focus on higher education-related research, and a review of student development research and application.
Include Index
Keywords: United States -- College student development programs -- College students--Psychology